Life Stories and Mental Health:: The Role of Identification Processes in Theory and Interventions - Westerhof, Gerben; Bohlmeijer, Ernst (Narrative Matters)

(untitled) (The University of New Brunswick, 2012)
The goal of this article is to explore the relations between narratives and mental health from a psychological perspective. We argue that a process of identification with personal experiences underlies narrative structures that are known to be related to mental health. Overidentification and underidentification are described as general processes underlying mental health problems. Gerontological insights in reminiscence and life review and cognitive psychological studies on autobiographical memories validate this claim. Practical applications in mental health care provide even further evidence for the role of identification processes in mental health and how they can be targeted in interventions.